Markers of discourse structure in digital crowdfunding science proposals - Vela-Rodrigo, Alberto A. (Complutense Journal of English Studies, 2024)
In a scientific context of growing interdependence at a global level, digital genres for public communication of science in the Internet are gaining scholarly attention. Yet, although these genres have been mainly examined through their rhetorical organisation and their main discourse features, research on the latter is to date limited. To fill this gap, this study focuses on the functions of linguistic markers of discourse structure in texts exemplars of science crowdfunding online. Overall results show that constructing a semantically coherent discourse is fundamental to achieve the main communicative purposes of this genre, namely to inform about science while requesting the public’s donations for carrying out a project. Results also show that linguistic markers of discourse structure are widely used for establishing contrast among ideas and concepts, and by this means build the argument and persuade the reader that it is important to finance the project. They also help the construction of a coherent academic discourse in every rhetorical section (Overview, Lab Notes, Discussion), exhibiting variation across them according to their communicative functions.